Analisis Teori Antrean untuk Menilai Kualitas Pelayanan pada Usaha Pangsit Chili Oil Menggunakan Model Saluran Tunggal-Fase Tunggal - Putri, Anastasya Alya; Utomo, Pradita Eko Prasetyo; Iftita, Hasanatul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This study examines the queuing system at the Pangsit Chili Oil business by implementing the Single-Phase Single Channel (M/M/1) model to broadcast service quality. Data collection was conducted on December 1, 2024 for five operating hours (11:00-16:00 WIB), involving a total of 49 customers. The analysis shows that the frequency of customer arrivals (λ) reached 9.8 people per hour, while the service rate (μ) was recorded at 14.27 people per hour. In this system, the utility (ρ) was found to be 68.7%, with an average queue size ranging from 1 to 2 customers and a waiting time of around 9 minutes. These findings indicate that the service system operates efficiently and has a spare capacity of 31.3% to handle customer transmission. From a practical perspective, the results of this study can be used by management to improve resource distribution, employee scheduling, and service area layout arrangements in order to maintain a balance between operational efficiency and customer satisfaction. This model also has the potential to be applied to other culinary businesses with similar operational characteristics, especially micro and small businesses that have limited resources. Future research could explore multi-channel queuing models to respond to business growth or the application of digital ordering technology to improve system efficiency.